Performance of the Mini Nutritional Assessment Score in the Detection of Vitamin D Status in an Elderly Greek Population - Tsagari, A.; Toulis, K. A.; Makras, P.; Skagias, K.; Galanos, A.; Lyritis, G. (Hormone and Metabolic Research, 2012)
The primary aim of the study was to explore the potential relationship between serum 25-hydroxyvitamin D [25(OH)D] levels and Mini Nutritional Assessment (MNA) score, a surrogate for protein energy undernutrition, in elderly (≥65 years old) subjects with and without a hip fracture. A secondary aim of the study was to provide estimates of the MNA discriminatory performance in the detection of subjects with low levels of 25(OH)D (<20 ng/ml). The study population consisted of 101 patients with a hip fracture, recruited from a single urban Hospital in Athens, Greece, and 85 community dwelling subjects with no history of hip fracture. Serum 25(OH)D was measured, nutritional status was determined by the MNA questionnaire in all subjects, and linear correlation between variables was investigated. Receiver operator characteristic (ROC) curve analysis was performed and discriminatory performance was further assessed by calculating positive and negative likelihood ratios (LR). MNA scores were significantly correlated with 25(OH)D levels (rho=0.685, p<0.001) and this finding was robust in both groups and unaffected by gender. ROC curve analysis demonstrated an area under the curve (AUC) of 0.860 [standard error (SE): 0.026, 95% confidence interval (CI): 0.810–0.910], which provided a significantly better estimation of 25(OH)D status than simple guess (p<0.001). The lowest cutoff value in MNA score, providing a sensitivity over 90% was 25.25, which was associated with a sensitivity of 90.9% and a specificity of 53.6%. The same analysis revealed acceptable results only within hip fracture patients. MNA score might be a satisfactory surrogate marker for 25(OH)D levels with which it is linearly correlated. However, it appears that its discriminatory performance, as a diagnostic tool for 25(OH)D insufficiency, is rather suboptimal.
Keywords: 25-hydroxyvitamin D [25(OH)D]; mini nutritional assessment; undernutrition; hip fracture; aging; osteoporosis